Profesionalitas Guru dalam Pendampingan Pembelajaran PPT Interaktif di MAN 2 Kota Makassar: Teacher Professionalism in Assisting Interactive PPT Learning at MAN 2 Makassar City - Nurul Mahmudah, Luthfiah; Jannah, Nur; Rosdiana (ISEDU : Islamic Education Journal, 2024)
This research was created to determine the professionalism of teachers in assisting Interactive PPT learning. The writing method is carried out using a type of qualitative research with various approaches, as a means of searching for and understanding a phenomenon. So that this research can find out central symptoms. To find out these central symptoms, this research activity will use interview and observation techniques. The research results show that using interactive power point media can make the learning process more interactive because students can use the media directly. Can save time and energy. Because the message conveyed by the teacher is helped by the existence of interactive media, it can improve the quality of student learning outcomes and can foster students' positive attitudes towards learning. Keywords: Teacher Professionalism, Learning Media and Interactive Power Point